Quinoline-2-carboxylic acid isolated from Ephedra pachyclada and its structural derivatives show inhibitory effects against α-glucosidase and α-amylase - Lee, Hwa-Won; Yang, Ji-Yeon; Lee, Hoi-Seon (Applied biological chemistry, 2014)
The aim of present study was to isolate a bioactive compound from the chloroform fraction of Ephedra pachyclada stems and to evaluate antidiabetic activities against α-glucosidase and α-amylase. According to various chromatographic and spectroscopic analyses, the bioactive compound of E. pachyclada was identified as quinoline-2-carboxylic acid. Based on the IC 50 values of quinoline-2-carboxylic acid derivatives against α-glucosidase and α-amylase, quinoline-2-carboxylic acid (9.1 and 15.5 μg/mL) exhibited potent inhibitory activities, followed by quinoline-3-carboxylic acid (10.6 and 31.4 μg/mL), quinoline-4-carboxylic acid (60.2 and 152.4 μg/mL), and acarbose (66.5 and 180.6 μg/mL) against α-glucosidase and α-amylase, respectively. However, quinoline-2-carboxaldehyde, quinoline-3-carboxaldehyde, and quinoline-4-carboxaldehyde showed no inhibitory activities. Antidiabetic activity depended on the existence of a carboxyl group on quinoline for activities against α-glucosidase and α-amylase. Therefore, E. pachyclada and quinoline-2-carboxylic acid derivatives could be suitable as alternative synthetic antidiabetic agents.